Historical Cartography (NE, Brazil): A Study of Coastal Geoforms Cartographed Post-Discovery - Farrapeira Neto, Carlos Araújo; Meireles, Antônio Jeovah Andrade; Paula, Davis Pereira; Barrera, Francisco Borja; Artigas, Rafael Cámara; Barrera, César Borja; Albuquerque, Miguel Guia; Amorim, Josafá Terto (Sociedade & Natureza, 2023)
Geomorphological studies are crucial for understanding the evolution of relief, and when associated with cartography, they enhance the interpretation and knowledge of environmental dynamics. Hence, historical cartography is essential for the documental rescue of landscapes, which, based on the mapped geoforms, enhances post-discovery studies for the state of Ceará, Brazil. Historically, this state was intermittently mapped in the sixteenth and seventeenth centuries but gained greater attention from Portugal in the eighteenth and nineteenth centuries after its separation from Pernambuco. Despite this, cartographic studies on coastal geoforms are not typical for the Ceará coast over a given period, highlighting the importance of this investigation. Therefore, this article aimed to study the environmental history of the coastal geoforms mapped on the extreme west coast of Ceará in the seventeenth and eighteenth centuries. This research had a qualitative and exploratory basis, with cartographic documental surveys online and in loco, covering the municipalities of Jijoca de Jericoacoara, Camocim, and Barroquinha. Fifty maps of different origins were collected, three of which were used: a French sketch and two Portuguese maps. In the French material of 1615, geoforms in the Cape de la Tortue indicated the presence of a rocky island separated from the mainland. From the Portuguese map of 1629, a well-cut coastline was noted, identifying Buraco das Tartarugas, where there were two islands of different sizes. In the 1794 map, an island in the cove called Geri qua Coá was noted, differing in landscape from the previous ones, as it did not have tombolos connected to the continent. The cartographies presented particularities for revealing a possible advance in the local sea level. Thus, it is possible to motivate future research in the area of historical cartography as a tool for the analysis of the paleogeographic evolution of the coastal zones of Ceará.